Structure-Dependent CO2 Gas Sensitivity of La2O2CO3 Thin Films. (11th July 2017) - Kodu, Margus; Avarmaa, Tea; Mändar, Hugo; Saar, Rando; Jaaniso, Raivo
Abstract : Rare earth oxycarbonates are potential candidate materials for constructing simple and low-cost chemiresistive sensors for monitoring carbon dioxide (CO2 ) gas in the living and working environment for personal comfort and health reasons. Also, measurement of CO2 concentrations is needed in many industrial processes. Specifically, sol-gel made nanoparticles of Nd and La oxycarbonates have been studied previously as novel CO2 gas sensor materials. In this paper, pulsed laser deposition of La oxycarbonate (La2 O2 CO3 ) thin films was studied and structural properties of obtained thin films were characterized. Also, CO2 gas sensing ability of synthesized films was evaluated. The films deposited under CO2 partial pressure in various conditions were all Raman amorphous. In situ or ex situ annealing procedure at high CO2 partial pressure was needed for obtaining crystalline La2 O2 CO3 films, whereby hexagonal and monoclinic polymorphs were obtained in ex situ and in situ processes, respectively. Sensor structure, made using in situ process, was sensitive to CO2 gas and showed relatively fast response and recovery characteristics.